Impact of fondaparinux versus enoxaparin on in-hospital bleeding and 1-year death in non-ST-segment elevation myocardial infarction. FAST-MI (French Registry of Acute ST-elevation and non-ST-elevation Myocardial Infarction) 2010. Issue 3 (1st June 2015) - Puymirat, Etienne; Schiele, François; Ennezat, Pierre-Vladimir; Coste, Pierre; Collet, Jean-Philippe; Bonnefoy-Cudraz, Eric; Roul, Gérald; Richard, Pascal; Simon, Tabassome; Danchin, Nicolas
Abstract: Aims: Fondaparinux is an alternative to low molecular weight heparin (LMWH) for non-ST-elevation myocardial infarction (NSTEMI) with levels of recommendation that differ according to guidelines. The aim of this study was to assess outcomes in real world practice in NSTEMI patients participating in the French Registry of ST-elevation and non-ST-elevation Myocardial Infarction (FAST-MI) 2010 according to the use of fondaparinux, in comparison with patients receiving enoxaparin. Methods and Results: FAST-MI 2010 is a nationwide French registry that included 4, 169 patients with acute myocardial infarction at the end of 2010 in 213 centres (76% of active centres in France); 1, 734 had NSTEMI, with 240 receiving fondaparinux and 1, 027 enoxaparin. Patients receiving enoxaparin vs. fondaparinux had essentially characteristics with a similar GRACE (Global Registry of Acute Coronary Events) score. Invasive strategy was used in 69% in both groups. In-hospital bleeding was similar with both anticoagulant strategies and 1-year survival was 94.6% and 91.7%, respectively. Using fully adjusted Cox multivariate analysis, the use of fondaparinux was not associated with a reduced risk of death (hazard ratio: 1.35; 95% confidence interval: 0.70–2.51). After propensity score matching (207 patients per group), 1-year survival was similar with both strategies. There was, however, an interaction between fondaparinux and unfractionated heparin, with higher survival in fondaparinux-treated patients who received UFH, compared with those who did not. Conclusions: In this French cohort of NSTEMI patients, predominantly managed invasively, there was no evidence that fondaparinux was superior to enoxaparin as regards bleeding events or 1-year mortality (FAST-MI 2010; NCT01237418).